Net Scan: Web-based Network Scanning Tool - Liang Foong, Lee; Juremi, Julia; Nathan, Yogeswaran (International Journal of Psychosocial Rehabilitation, 2019)
Cyber security has been highlighted in recent years due to the increasing number of cyber-attacks and the impact it can cause which affect national security. To improve cyber security, network scanning tools are essential where it is used for gathering information about the actual state of a system or network. Therefore, we will examine common modules included in a network scanning tool and 6 common port scanning techniques. In this paper, the differences of existing and proposed system will also be discussed where the proposed system is a webbased network scanning tool named Net Scan which is able to perform host discovery, operating system detection, open ports and services, and trace route